Application of 1.0-μm macroporous hollow fiber membrane for prevention of membrane fouling and enhancement of permeate flux in algae harvesting. (February 2022) - Yamamura, Hiroshi; Matsumoto, Takaki; Goto, Keisuke; Ding, Qing; Kuroiwa, Miho; Harayama, Shigeaki
Abstract: We challenged to introduce macroporous membrane for algae harvesting with a permeate flux of 166 L m −2 d −1 to achieve significant reduction of harvesting cost. Analysis of the dissolved organic matter in the supernatant of cultures of the green alga, Coccomyxa sp. strain Obi, detected a scarce amount of hydrophilic macromolecules, which can be membrane fouling agents. The continuous filtration with a macroporous membrane achieved a 30-fold concentration of algal cells from 800 mg biomass/L to 24, 000 mg biomass/L with a harvesting efficiency of 100%. Most of previous studies on the membrane filtration for harvesting microalgae merely utilized microfiltration membranes developed for wastewater treatment. However, the use of a membrane of the largest pore size that microalgal cells cannot seep through will result in slower fouling, higher flux, and a great reduction of harvesting cost. Graphical abstract: Unlabelled Image Highlights: Vast majority of cells were between 2 and 8 μm in diameter. Major carbohydrate fraction consisted of molecules weighing less than 10 kDa. Caked Microalgae were effectively removed by backwashing at 90 kPa for 5 s. Membrane could concentrate Coccomyxa by 30-fold under optimized conditions. Total OPEX and CAPEX were estimated at $0.25/kg-algae.